Association of depression and psychotropic medication on cardiac-related outcomes in a nationwide community-dwelling elderly population in Taiwan. Issue 31 (August 2016) - Hsu, Wen-Yu; Tsai, Hui-Ju; Yu, Shu-Han; Hsu, Chih-Cheng; Tsai, Yu-Ting; Tzeng, Han-Yun; Lin, I-Ching; Liu, Kiang; Lee, Marion M.; Chiu, Nan-Ying; Hsiung, Chao A.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The objective of this study was to examine the association of depression, psychotropic medications, and mental illness with cardiovascular disease in a nationwide community-dwelling elderly population in Taiwan. A total of 5664 participants who enrolled in the Healthy Aging Longitudinal Study in Taiwan (HALST) were included in the study. Multiple logistic regression was applied to investigate the association of depression, psychotropic medication use, and mental illness, separately, with cardiovascular disease. The results suggested that cardiovascular disease was significantly associated with various definitions of depression, including: the Center for Epidemiologic Studies-Depression scale (CES-D) ≥ 16, self-reported, and physician-diagnosed for depression (adjusted odds ratio [AOR] = 1.51; 95% confidence interval (CI): 1.14–2.00 for CES-D; AOR = 3.29; 95% CI: 1.99–5.42 for self-reported; and AOR = 2.45; 95% CI: 1.51–3.97 for physician-diagnosed). Additionally, significant associations of cardiovascular disease with the use of antipsychotics (AOR = 2.04; 95% CI: 1.25–3.34), benzodiazepines (BZDs) (AOR = 1.84; 95% CI: 1.52–2.21), and Z-drugs (AOR = 1.41; 95% CI: 1.03–1.93), respectively, were also observed, but not the use of antidepressants. In addition, a significant association of cardiovascular disease with mental illness was found in this study (AOR = 2.33; 95% CI: 1.68–3.24). In line with previous reports, these findings provided supportive evidence that depression and/or mental illness were significantly associated with cardiovascular disease in a community-dwelling elderly population in Taiwan. Moreover, significant associations of cardiovascular disease with the use of antipsychotics, BZDs, and Z-drugs, individually, were found. Further investigation would be of importance to clarify the causal relationship of depression and/or psychotropic medications with cardiovascular disease, especially among elderly populations.